Предмет: Алгебра,
автор: alenazvyagina91
(9ˣ-2·3ˣ⁺¹)²₊14(9ˣ₋2·3ˣ⁺¹)≥0
Ответы
Автор ответа:
0
(9ˣ-2·3ˣ⁺¹)²₊14(9ˣ₋2·3ˣ⁺¹)≥0
(9ˣ-6·3ˣ)²₊14(9ˣ₋6·3ˣ)≥0
9ˣ₋6·3ˣ = z
z² + 14z ≥ 0
z(z + 14) ≥ 0
++++++++[-14] -------------- [0] +++++++++
1. z ≤ - 14
9ˣ₋6·3ˣ ≤ -14
9ˣ₋6·3ˣ +14 ≤ 0
9ˣ = 3²ˣ
D = 36 - 4*14 < 0
Ветви вверх
D < 0
решений нет
2. z ≥ 0
9ˣ₋6·3ˣ ≥ 0
3ˣ(3ˣ - 6) ≥ 0
3ˣ - 6 ≥ 0
x ≥ log(3) 6
Ответ x ≥ log(3) 6
Похожие вопросы
Предмет: Английский язык,
автор: vkalzan
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: 303035
Предмет: Химия,
автор: karim28
Предмет: Литература,
автор: vadimagap2002